Space exploration by dendritic cells requires maintenance of myosin II activity by IP3 receptor 1. (30th January 2015) - Solanes, Paola; Heuzé, Mélina L; Maurin, Mathieu; Bretou, Marine; Lautenschlaeger, Franziska; Maiuri, Paolo; Terriac, Emmanuel; Thoulouze, Maria‐Isabel; Launay, Pierre; Piel, Matthieu; Vargas, Pablo; Lennon‐Duménil, Ana‐Maria
Abstract Dendritic cells (DCs) patrol the interstitial space of peripheral tissues. The mechanisms that regulate their migration in such constrained environment remain unknown. We here investigated the role of calcium in immature DCs migrating in confinement. We found that they displayed calcium oscillations that were independent of extracellular calcium and more frequently observed in DCs undergoing strong speed fluctuations. In these cells, calcium spikes were associated with fast motility phases. IP3 receptors (IP3Rs) channels, which allow calcium release from the endoplasmic reticulum, were identified as required for immature DCs to migrate at fast speed. The IP3R1 isoform was further shown to specifically regulate the locomotion persistence of immature DCs, that is, their capacity to maintain directional migration. This function of IP3R1 results from its ability to control the phosphorylation levels of myosin II regulatory light chain (MLC) and the back/front polarization of the motor protein. We propose that by upholding myosin II activity, constitutive calcium release from the ER through IP3R1 maintains DC polarity during migration in confinement, facilitating the exploration of their environment.